Estimating the resources required in the roll-out of universal access to antiretroviral treatment in Zimbabwe. Issue 7 (2nd June 2011) - Hallett, T B; Gregson, S; Dube, S; Mapfeka, E S; Mugurungi, O; Garnett, G P
Abstract : Objectives: To develop projections of the resources required (person-years of drug supply and healthcare worker time) for universal access to antiretroviral treatment (ART) in Zimbabwe. Methods: A stochastic mathematical model of disease progression, diagnosis, clinical monitoring and survival in HIV infected individuals. Findings: The number of patients receiving ART is determined by many factors, including the strategy of the ART programme (method of initiation, frequency of patient monitoring, ability to include patients diagnosed before ART became available), other healthcare services (referral rates from antenatal clinics, uptake of HIV testing), demographic and epidemiological conditions (past and future trends in incidence rates and population growth) as well as the medical impact of ART (average survival and the relationship with CD4 count when initiated). The variations in these factors lead to substantial differences in long-term projections; with universal access by 2010 and no further prevention interventions, between 370 000 and almost 2 million patients could be receiving treatment in 2030—a fivefold difference. Under universal access, by 2010 each doctor will initiate ART for up to two patients every day and the case-load for nurses will at least triple as more patients enter care and start treatment. Conclusions: The resources required by ART programmes are great and depend on the healthcare systems and the demographic/epidemiological context. This leads to considerable uncertainty in long-term projections and large variation in the resources required in different countries and over time. Understanding how current practices relate to future resource requirements can help optimise ART programmes and inform long-term public health planning.